2022
DOI: 10.1007/s00784-022-04493-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of concentrated growth factor versus collagen membrane in reconstructive surgical therapy of peri-implantitis: 3-year results of a randomized clinical trial

Abstract: Objectives To compare the 3-year clinical and radiographic outcomes of two different reconstructive surgical management of peri-implantitis using a bone substitute in combination with either concentrated growth factor (CGF) or collagen membrane (CM). Material and methods Fifty-one patients who had at least one implant presenting peri-implantitis with an intrabony defect were filled with a xenogenic bone grafting material and covered either CGF or CM. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 53 publications
2
52
0
Order By: Relevance
“…Only two studies specifically referred to the European Federation of Periodontology (EFP) definition of peri-implantitis (Isler et al, 2018;Gonzalez Regueiro et al, 2021;Isler et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies specifically referred to the European Federation of Periodontology (EFP) definition of peri-implantitis (Isler et al, 2018;Gonzalez Regueiro et al, 2021;Isler et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of platelet rich fibrin (PRF) membranes on peri‐implant bone regeneration was observed in a recent RCT with a 3‐year follow‐up. The use of a CM compared to PRF membrane in combination with a bone substitute in surgical peri‐implantitis therapy revealed that the CM group led to a larger decrease in PPD and slightly better outcomes compared to the PRF membranes 80 …”
Section: Resultsmentioning
confidence: 99%
“…The use of a CM compared to PRF membrane in combination with a bone substitute in surgical peri-implantitis therapy revealed that the CM group led to a larger decrease in PPD and slightly better outcomes compared to the PRF membranes. 80…”
Section: Growth Factorsmentioning
confidence: 99%
“…In addition, the application of xenogenic bone filler in combination with a resorbable collagen membrane displayed more predictable outcomes in terms of disease resolution than the application of a synthetic bone filler alone 57 . Furthermore, comparison of a concentrated growth‐factor membrane to a collagen membrane along with xenogenic bone filler resulted in greater PD reduction, whereas changes in BOP and radiographic defect fill were similar between the two treatment groups 27,31 …”
Section: Reconstructive Therapymentioning
confidence: 98%